Overview Of Knowledge Of Women Of Fertilizing Age About Being Conscious In Sampungu Village, Soromandi District, Bima District, 2023 - Nur Islamyati; Suryati, Suryati (Jurnal EduHealth, 2023)
Breast cancer is the main cause of cancer death in women throughout the world. High breast cancer mortality has been attributed to a lack of public awareness of the disease. The Dompu District Health Service shows that the incidence of breast cancer in 2020 was 276 cases. in 2021 there were 8107 cases and in 2022 the number of 16,261 increased, one of the causes was the mother's lack of knowledge about early detection through the BSE technique (Bima District Health Service, 2023).. Objective This research seeks to describe the knowledge of women of childbearing age about BSE in the work area of Sampungu village, Soromandi sub-district, Bima district. Research Methods This research uses a simple descriptive design.. The design used is to describe variables and phenomena which are then interpreted. This descriptive design will explain to researchers the description of women's knowledge about the childbearing age of BSE in Sampungu Village, Bima Regency in 2023, as many as 50 people. The analysis of this research is univariate analysis. The Instrument used is a questionnaire. Conclusion The results of this study showed a significant relationship between knowledge of women of childbearing age about BSE and breast cancer in the working area of Sampungu Village, Soromandi District, Bima Regency. Suggestion Services in the Rasabou Community Health Center working area in Hu'u subdistrict should be able to prevent the lack of knowledge of women of childbearing age about BSE by carrying out outreach activities, providing clear information that is easy to understand and recommending that women of childbearing age carry out BSE techniques regularly.